Avoidance of CNI and steroids using belatacept—Results of the Clinical Trials in Organ Transplantation 16 trial. Issue 12 (13th July 2020) - Mannon, Roslyn B.; Armstrong, Brian; Stock, Peter G.; Mehta, Aneesh K.; Farris, Alton B.; Watson, Natasha; Morrison, Yvonne; Sarwal, Minnie; Sigdel, Tara; Bridges, Nancy; Robien, Mark; Newell, Kenneth A.; et al.
Abstract : Immunosuppression devoid of corticosteroids has been investigated to avoid long‐term comorbidities. Likewise, alternatives to calcineurin inhibitors have been investigated as a strategy to improve long‐term kidney function following transplanion. Costimulatory blockade strategies that include corticosteroids have recently shown promise, despite their higher rates of early acute rejection. We designed a randomized clinical trial utilizing depletional induction therapy to mitigate early rejection risk while limiting calcineurin inhibitors and corticosteroids. This trial, Clinical Trials in Organ Transplantation 16 (CTOT‐16), sought to evaluate novel belatacept‐based strategies employing tacrolimus and corticosteroid avoidance. Sixty‐nine kidney transplant recipients were randomized from 4 US transplant centers comparing a control group of with rabbit antithymocyte globulin (rATG) induction, rapid steroid taper, and maintenance mycophenolate and tacrolimus, to 2 arms using maintenance belatacept. There were no graft losses but there were 2 deaths in the control group. However, the trial was halted early because of rejection in the belatacept treatment groups. Serious adverse events were similar across groups. Although rejection was not uniform in the belatacept maintenance therapy groups, the frequency of rejection limits the practical implementation of this strategy to avoid both calcineurin inhibitors and corticosteroids at this time. Abstract : In the Clinical Trials in Organ Transplant‐16 trial, T cell depletional induction, followed by a belatacept‐based immunosuppressive regimen free of maintenance corticosteroids and tacrolimus, is associated with higher than expected rates of acute rejection, which led to early trial closure.